Improving risk assessment of color additives in medical device polymers. Issue 1 (31st January 2017) - Chandrasekar, Vaishnavi; Janes, Dustin W.; Forrey, Christopher; Saylor, David M.; Bajaj, Akhil; Duncan, Timothy V.; Zheng, Jiwen; Riaz Ahmed, Kausar B.; Casey, Brendan J.
Abstract: Many polymeric medical device materials contain color additives which could lead to adverse health effects. The potential health risk of color additives may be assessed by comparing the amount of color additive released over time to levels deemed to be safe based on available toxicity data. We propose a conservative model for exposure that requires only the diffusion coefficient of the additive in the polymer matrix, D, to be specified. The model is applied here using a model polymer (poly(ether‐ block ‐amide), PEBAX 2533) and color additive (quinizarin blue) system. Sorption experiments performed in an aqueous dispersion of quinizarin blue (QB) into neat PEBAX yielded a diffusivity D = 4.8 × 10 −10 cm 2 s −1, and solubility S = 0.32 wt %. On the basis of these measurements, we validated the model by comparing predictions to the leaching profile of QB from a PEBAX matrix into physiologically representative media. Toxicity data are not available to estimate a safe level of exposure to QB, as a result, we used a Threshold of Toxicological Concern (TTC) value for QB of 90 µg/adult/day. Because only 30% of the QB is released in the first day of leaching for our film thickness and calculated D, we demonstrate that a device may contain significantly more color additive than the TTC value without giving rise to a toxicological concern. The findings suggest that an initial screening‐level risk assessment of color additives and other potentially toxic compounds found in device polymers can be improved. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 310–319, 2018.